2020
DOI: 10.1002/jmv.26274
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence of hepatitis E virus in children from Northeast of Argentina

Abstract: The aim of this study was to assess the prevalence of hepatitis E virus (HEV) in a young population from the Northeast region of Argentina. Four hundred and twelve patients under 18 years old, from rural areas of Chaco Province, were tested for anti‐HEV immunoglobulin G (IgG) using enzyme‐linked immunosorbent assay. Anti‐HEV IgG antibodies were detected in 7 out of 412 patients, accounting for an overall 1.7% prevalence. HEV infection in developing countries is associated to lack of clean drinking water. Conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Results also showed a significantly higher prevalence in males than females with an odds ratio of two for being a male (29.44 vs. 17.29%, p < 0.001). Older age and male gender were reported in several other studies as associated risk factors for the high prevalence of HEV in different populations [ 38 , 46 , 47 ]. The living conditions of the recruited subjects played an important role in the spread of the infection, as shown by the higher seroprevalence of HEV in participants living in shared housing and villas (with or without gardens) ( p < 0.001), in housing where water supply is not available ( p = 0.032), and in housing where water supply is irregular ( p = 0.002).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Results also showed a significantly higher prevalence in males than females with an odds ratio of two for being a male (29.44 vs. 17.29%, p < 0.001). Older age and male gender were reported in several other studies as associated risk factors for the high prevalence of HEV in different populations [ 38 , 46 , 47 ]. The living conditions of the recruited subjects played an important role in the spread of the infection, as shown by the higher seroprevalence of HEV in participants living in shared housing and villas (with or without gardens) ( p < 0.001), in housing where water supply is not available ( p = 0.032), and in housing where water supply is irregular ( p = 0.002).…”
Section: Discussionmentioning
confidence: 83%
“…Teixeira et al also reported a relatively high prevalence rate in Portugal from a lower sample size (19.9% from 804 participants) [ 7 ]. Other studies from Germany (two studies), Spain, the USA (two studies), and the Czech Republic showed a prevalence rate ranging from 2.17% to 16.8% [ 42 , 43 , 44 , 45 , 46 ]. Collectively, these studies demonstrate how the seroprevalence rate of HEV may substantially vary from one country to another.…”
Section: Discussionmentioning
confidence: 99%
“…Our low HEV seroprevalence is in line with the few other studies performed in children in Latin America ( 57 ). While the first of two studies conducted in Argentina found a crude HEV IgG seroprevalence of 0.15% in participants from urban Buenos Aires with a mean age of 6.4 ( 58 ), the second one found a crude seroprevalence of 1.7% in participants from the rural Chaco Province with a median age of 14 years ( 59 ). HEV crude seroprevalence in children from urban Santa Cruz, Bolivia was 1.7% (95% CI: 1.5–1.8%) ( 60 ), in which all HEV IgG-reactive participants were exclusively from the poorest social class and between 13 and 18 years old.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, sporadic cases of acute and chronic hepatitis E have been reported [ 5 ], and HEV-3 RNA has been detected in environmental (sewage, dam and river) and animal (pigs and wild boards) samples [ 5 ]. Only two previous studies of HEV circulation in children have been performed in our country, reporting seroprevalences of 0.15 % and 1.7 % [ 8 , 9 ]. However, one of them was performed in the 1990s decade [ 8 ], and the other one (performed between 2016 and 2018) was localized to a rural area in the North of the country (Chaco province) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%